Inadequate School Facilities: It’s Effect on the Learning Experience of the Selected Students in Jolo National High School - Eloiza M. Mohammad (Future Science / FSH-PH Publications, 2026)
In particular, the study examined both the state of and access to school facilities as well as how these physical learning environments affect students’ academic experiences and engagement. The study assumed that adequacy and quality of school infrastructure will significantly affect students’ motivation, safety among others resulting to better learning. Using a descriptive statistical research design, the current status of school facilities and their perceived impact on learning were determined. The study’s respondents were 120 Grade 10 students of Jolo National High School from whom data were taken. The first part of the research instrument included collecting demographic profile of the respondents, while part II focused on ascertaining students’ perspective towards school facilities and learning experiences. We discovered that the physical state of a school’s learning environment influences students’ learning experiences. There was strong agreement that neatness, cleanliness and structural well-being were critical to effective teaching, motivation to excel academically and inspection of the students in schools. That said, the study flagged issues with schools having insufficient and poorly maintained facilities that block classroom instruction, participation and engagement in education. Broader discourses surrounding learning environments and academic resources also find a place in these results, illustrating how physical infrastructure of the learning environment, as well as supportive educational tools play key roles in improving student learning experiences, an idea that is pervaded by the scoping review regarding the academic resources brought to light by Pangandaman et al. (2025).